2005
DOI: 10.1212/01.wnl.0000152980.92436.d9
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic evidence for absence of the facial nerve in Möbius syndrome

Abstract: The absent facial nerves on MRI and the unusual distribution of the facial weakness, which is characteristic of Möbius syndrome, suggests that other cranial nerves, possibly the trigeminal, hypoglossal, or glossopharyngeal nerve, aberrantly innervate some lower facial muscles. Radiologic findings support the notion that Möbius syndrome is part of a more complex congenital anomaly of the fossa posterior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 30 publications
2
26
0
2
Order By: Relevance
“…Of these six, four had bilateral Type 3 Duane syndrome. 6 The nature and extent of the facial palsy, along with unilateral absence of facial nerve, are consistent with the diagnosis of Möbius' syndrome. The asymmetric "crossed" facial diplegia with the upper part being affected more on the left side and the lower part affected more on the right side could possibly be due to aberrant innervation of the lower facial musculature on the left side by the fifth, ninth, or twelfth cranial nerves, has been described in Möbius variants.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Of these six, four had bilateral Type 3 Duane syndrome. 6 The nature and extent of the facial palsy, along with unilateral absence of facial nerve, are consistent with the diagnosis of Möbius' syndrome. The asymmetric "crossed" facial diplegia with the upper part being affected more on the left side and the lower part affected more on the right side could possibly be due to aberrant innervation of the lower facial musculature on the left side by the fifth, ninth, or twelfth cranial nerves, has been described in Möbius variants.…”
Section: Discussionsupporting
confidence: 56%
“…The asymmetric "crossed" facial diplegia with the upper part being affected more on the left side and the lower part affected more on the right side could possibly be due to aberrant innervation of the lower facial musculature on the left side by the fifth, ninth, or twelfth cranial nerves, has been described in Möbius variants. 6 Features of oculoauriculovertebral spectrum/hemifacial microsomia include epibulbar dermoids, facial hypoplasia, vertebral anomalies, and varying ear deformities ranging from anotia to preauricular skin-tags. Both bilateral and unilateral cases of Duane syndrome have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…CT or MRI imaging shows hypoplasia of the lower brainstem as well as other cerebral malformations including the absence of the middle cerebellar peduncles and the thinning of the corpus callosum [4,7,22,23]. Microcalcifications may be present in locations adjacent to the abducens nuclei possibly indicative of ischemic destruction [4,18,22,24].…”
Section: Radiographic Findingsmentioning
confidence: 99%
“…Other cranial neuropathies can also be found, most notably cranial nerves V, IX, X, and XII [4][5][6]. Some patients retain residual lower facial muscle activity suggesting aberrant innervation from other cranial nerves; some studies have suggested the possibility of cranial nerves V, IX, and XII [7]. Other abnormalities include lingual hypoplasia, sensorineural hearing loss, craniofacial malformations (epicanthic folds, micrognathia), and abnormalities of the extremities (syndactyly, pes planus, valgus femur) [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…46 Moebius syndrome is characterized by facial weakness and impairment of ocular abduction and is frequently bilateral. 48 These patients often have hypoplasia or agenesis of the CN VII nuclei and the accompanying facial nerve along with brainstem hypoplasia (Fig 16). Patients with Goldenhar syndrome demonstrate unilateral CFNP associated with vertebral defects, facial hypoplasia, and preauricular skin tags.…”
Section: Congenitalmentioning
confidence: 99%